Syncopes and clinical outcome in heart failure: results from prospective clinical study data in Germany - Djawid Hashemi; Moritz Blum; Meinhard Mende; Stefan Störk; Christiane E. Angermann; Sabine Pankuweit; Elvis Tahirovic; Rolf Wachter; Burkert Pieske; Frank Edelmann; Hans‐Dirk Düngen; the German Competence Network for Heart Failure (ESC Heart Failure)
Abstract Aims Whereas syncopal episodes are a frequent complication of cardiovascular disorders, including heart failure (HF), little is known whether syncopes impact the prognosis of patients with HF. We aimed to assess the impact of a history of syncope (HoS) on overall and hospitalization‐free survival of these patients. Methods and results We pooled the data of prospective, nationwide, multicentre studies conducted within the framework of the German Competence Network for Heart Failure including 11 335 subjects. Excluding studies with follow‐up periods <10 years, we assessed 5318 subjects. We excluded a study focusing on cardiac changes in patients with an HIV infection because of possible confounding factors and 849 patients due to either missing key parameters or missing follow‐up data, resulting in 3594 eligible subjects, including 2130 patients with HF [1564 patients with heart failure with reduced ejection fraction (HFrEF), 314 patients with heart failure with mid‐range ejection fraction, and 252 patients with heart failure with preserved ejection fraction (HFpEF)] and 1464 subjects without HF considered as controls. HoS was more frequent in the overall cohort of patients with HF compared with controls (P < 0.001)—mainly driven by the HFpEF subgroup (HFpEF vs. controls: 25.0% vs. 12.8%, P < 0.001). Of all the subjects, 14.6% reported a HoS. Patients with HFrEF in our pooled cohort showed more often syncopes than subjects without HF (15.0% vs. 12.8%, P = 0.082). Subjects with HoS showed worse overall survival [42.4% vs. 37.9%, hazard ratio (HR) = 1.21, 99% confidence interval (0.99, 1.46), P = 0.04] and less days alive out of hospital [HR = 1.39, 99% confidence interval (1.18, 1.64), P < 0.001] compared with all subjects without HoS. Patients with HFrEF with HoS died earlier [30.3% vs. 41.6%, HR = 1.40, 99% confidence interval (1.12, 1.74), P < 0.001] and lived fewer days out of hospital than those without HoS. We could not find these changes in mortality and hospital‐free survival in the heart failure with mid‐range ejection fraction and HFpEF cohorts. HoS represented a clinically high‐risk profile within the HFrEF group—combining different risk factors. Further analyses showed that among patients with HFrEF with HoS, known cardiovascular risk factors (e.g. age, male sex, diabetes mellitus, and anaemia) were more prevalent. These constellations of the risk factors explained the effect of HoS in a multivariable Cox regression models. Conclusions In a large cohort of patients with HF, HoS was found to be a clinically and easily accessible predictor of both overall and hospitalization‐free survival in patients with HFrEF and should thus routinely be assessed.